307 Patients expectations of benefits from large-panel genomic tumor testing in rural community oncology practices. (April 2022) - Anderson, Eric C.; DiPlazzo, John; Rueter, Jens; Han, Paul
Abstract : OBJECTIVES/GOALS: Large-panel genomic tumor testing (GTT) is a new technology that promises to make cancer treatment more precise. However, patients may have unrealistic expectations of its benefits. The goal of this project is to assess expectations for GTT among cancer patients in community oncology practices. METHODS/STUDY POPULATION: A survey assessing expectations of the benefits of GTT was administered to cancer patients participating in a statewide study of GTT implementation, prior to receiving test results. Descriptive and regression analyses were conducted to assess expectations and the factors associated with these expectations. The study sample (N = 1, 139) consisted of patients with a range of cancer types (22% gynecologic, 14% lung, 10% colon, 10% breast, and 46% other malignancies). Mean age was 64 years (standard deviation = 11); 668 (59%) were women; 71% had no college degree; 57% came from households with less than $50, 000 US dollars household income; and 73% lived in a rural area. RESULTS/ANTICIPATED RESULTS: Generally, patients had high expectations that they would benefit from GTT (M = 2.81 on 0-4 scale) and positive attitudes toward it (M = 2.98 on 0-4 scale). Patients also had relatively poor knowledge about GTT (48% correct answers on an objective test of GTT knowledge). Greater expectations for GTT were associated with lower knowledge (b = –0.46; p < .001), more positive attitudes (b = 0.40; < .001), and lower education (b = –0.53; < .001). DISCUSSION/SIGNIFICANCE: This research suggests patients have high expectations that they will benefit from GTT, which is associated with low knowledge, positive attitudes, and low education. Interventions may be needed to boost understanding and moderate expectations, particularly for disadvantaged patients.